Softening Behavior and Mechanism of Laser Rapid Forming Ti-6Al-4V Alloy Deformed at the High Temperature. (September 2020) - Sun, Kun; Xiang, Wenli; Xu, Yuan; Shu, Xinzhu
Abstract: Using the gleeble-1500 thermal simulator, the high temperature quasi-static compression experiment on cylindrical samples of Laser Rapid Forming Ti-6Al-4V(LRF TC4) titanium alloy have been conducted. Softening behaviour and mechanism of LRF TC4 alloy deformed at different high temperatures were investigated by means of optical microscope (OM) and transmission electron microscope (TEM). It shows that, the strength of LRF TC4 was observably reduced with the rise of the deforming temperature, showing stronger thermal softening effect and superplasticity ability. Microstructure analysis on the samples deformed at the temperature from 400°C to 900°C showed that the original acicular microstructure of LRF TC4 has two significant changes: Acicular microstructure bents at the temperature from 400°C to 600°C, while acicular microstructure bents drasticly, fragmented, spheroidized at the temperature from 700°C to 900°C. No matter bending, fragmentation, or spheroidizing of acicular microstructure, stress in the deformed sample is released. Therefore, these three factors and their superimposition action were the source of thermal softening of LRF TC4 deformed at the high temperature.